Perlindungan Hukum terhadap Hak atas Upah Lembur Pekerja dalam Perselisihan Hubungan Industrial: Studi Putusan Nomor 39/Pdt.Sus-Phi/2025/Pn Sby - Khairunnisa Ananda Putri; Muhamad Abas; Yuniar Rahmatiar (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Legal guarantees for workers include the right to overtime pay, which employers must pay if workers work beyond the specified working hours. However, violations of this right still frequently occur, as seen in case No. 39/Pdt.SusPHI/2025/PN Sby. This study examines the legal guarantees for overtime pay based on the Manpower Law Regulations in conjunction with the Job Creation Law and the judge's considerations in the decision. The results of the study indicate that legal protection for overtime pay has been comprehensively regulated in legislation. The judge's considerations are deemed appropriate because they are based on valid facts and evidence. The Labor Inspectorate determined the company's liability at Rp18,643,500.00.